The relationship between the Geriatric Nutritional Risk Index and all-cause mortality in patients with peripheral artery disease. - Zhe Wu; Yue Yu; Bin Wang (PLoS ONE)
Background Peripheral artery disease (PAD) is a common atherosclerotic condition that leads to limb dysfunction and increases mortality risk. Malnutrition is closely related to the long-term mortality of PAD patients. Therefore, studying the relationship between the Geriatric Nutritional Risk Index (GNRI) and long-term mortality in patients with PAD is crucial for identifying high-risk populations and developing targeted interventions. Methods Data were sourced from the National Health and Nutrition Examination Survey (NHANES) conducted between 1999-2004, including 532 PAD patients. Kaplan-Meier survival analysis and multivariate Cox regression models assessed the relationship between GNRI and all-cause mortality in PAD patients. Subgroup analyses were conducted to explore differences based on demographic and disease backgrounds. Results During the follow-up period, a total of 415 all-cause deaths were recorded. The Kaplan-Meier survival curve showed significant differences in mortality rates between the different GNRI quartile groups. Multivariate Cox regression analysis showed a significant negative correlation between GNRI and the long-term mortality risk of PAD patients (HR: 0.950, 95%CI: 0.918, 0.983). Compared to the first GNRI quartile, PAD patients in the third (HR: 0.569, 95%CI: 0.357, 0.909) and fourth (HR: 0.396, 95%CI: 0.208, 0.751) quartiles had a significantly reduced risk of long-term mortality. Restrictive cubic spline analysis showed a significant linear negative correlation between GNRI and all-cause mortality in PAD patients. The subgroup analysis results showed that the negative correlation between GNRI and all-cause mortality in PAD patients was significant in all subgroups except for the female subgroup, subgroup with ABI > 0.7, subgroup without smoking history, and subgroup without hypertension. Conclusion There is a significant negative association between GNRI and all-cause mortality in PAD patients, suggesting that malnutrition may be a key factor affecting the prognosis of PAD patients. Early identification and intervention for malnutrition could reduce long-term mortality risks. Future research should further explore the role of nutritional interventions in the management of PAD and validate the findings of this study.